Determining the Risk of occupational exposure to benzene, toluene among gasoline stations workers, case study in selected gasoline stations in Kerman, Iran - A nasri; B jebelli; T nasrabadi; H hadizadeh; E ghazanchaei (طب کار)
Introduction: Benzene, Toluene, Ethyl Benzene and Xylene (BTEX) are Volatile Organic Compounds (VOCs) with similar physical and chemical characteristics. BTEX existing in gasoline releases to the air in result of the gasoline evaporation and the staffs are exposure to it in gasoline stations. The main goal of this project is to determine the risk of occupational exposure to BTEX compounds among workers in selected gasoline stations in Kerman and calculate the quantitative cancer and non cancer risk values of these defined compounds. Methodology: To achieve this goal, the air sample of 54 workers in 6 gasoline stations (the suburbs and downtown) were collected in three times morning, noon and night (that the fuel is discharged from the fuel tanker to the gasoline tank, in one of these three times) by sampling pumps. The samples were then transferred to the laboratory and analyzed by Gas Chromatography (GC) with a Flame Ionization Detector (FID). Result: The findings represent that the average concentration of BT during discharging the fuel from the tanker to the gasoline tank is higher than the average concentration of BT in the rest of sample. The Cancer risk for workers exposed to benzene is estimated in the range of 1.11×10- 2 – 8.22×10- 4. A quantitative non-cancer risk values for benzene, Toluene is also calculated in the range of 134-9.83, 0.699- 0.217. Conclusions: The results shows that the average concentrations of benzene in the air is higher than permissible limit proposed by Technical Committee of Occupational Hygiene (0.5 ppm or 1,600 μg/m 3), While Toluene are less than the permissible limit. As well, it is shown that the cancer risk benzene is high among workers in studied gasoline stations.